2019
DOI: 10.1177/2045894019881954
|View full text |Cite
|
Sign up to set email alerts
|

Orotracheal treprostinil administration attenuates bleomycin‐induced lung injury, vascular remodeling, and fibrosis in mice

Abstract: Pulmonary fibrosis is a progressive disease characterized by disruption of lung architecture and deregulation of the pulmonary function. Prostacyclin, a metabolite of arachidonic acid, is a potential disease mediator since it exerts anti-inflammatory and anti-fibrotic actions. We investigated the effect of treprostinil, a prostacyclin analogue, in bleomycin-induced experimental pulmonary fibrosis. Bleomycin sulfate or saline was administrated intratracheally to mice ( n = 9–10/group) at day 0. Orotracheal aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…A similar protective effect was found in rats submitted to inhalation of nanoparticle INS1009 containing treprostinil (IP agonist) prodrug (C16TR), which inhibited bleomycin-induced pulmonary fibrosis ( Corboz et al, 2018 ). In other studies, iloprost and treprostinil protected against bleomycin-induced pulmonary fibrosis ( Zhu et al, 2011 ; Nikitopoulou et al, 2019 ). In both studies, mice treated with bleomycin+iloprost showed a normal alveolar structure and reduced lung inflammation compared with those treated with bleomycin alone, with lower proinflammatory cytokine (TNF- α , IL-6, TGF- β 1) concentrations in broncho-alveolar lavage reported in the former study and reduced inflammatory cell infiltration in the latter.…”
Section: Respiratory Systemmentioning
confidence: 80%
“…A similar protective effect was found in rats submitted to inhalation of nanoparticle INS1009 containing treprostinil (IP agonist) prodrug (C16TR), which inhibited bleomycin-induced pulmonary fibrosis ( Corboz et al, 2018 ). In other studies, iloprost and treprostinil protected against bleomycin-induced pulmonary fibrosis ( Zhu et al, 2011 ; Nikitopoulou et al, 2019 ). In both studies, mice treated with bleomycin+iloprost showed a normal alveolar structure and reduced lung inflammation compared with those treated with bleomycin alone, with lower proinflammatory cytokine (TNF- α , IL-6, TGF- β 1) concentrations in broncho-alveolar lavage reported in the former study and reduced inflammatory cell infiltration in the latter.…”
Section: Respiratory Systemmentioning
confidence: 80%
“…We carried out lung function measurements to further evaluate the changes of pulmonary function-in silica-induced PF in mice, along with the protective effects of hucMSC-Exos by FOT measurements objectively. FOT measurements are an invasive method that can measure relevant parameters physiologically and describe the mechanical properties of the respiratory system accurately, which have been used to explore pathophysiological changes associated with fibrosis in mice models of respiratory diseases [ 29 , 30 ]. The classical parameters of respiratory mechanics, resistance, and compliance are related to the resistance of air in and out of the lungs as well as the expandability of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for pulmonary fibrosis typically involves administration of either oral pirfenidone (a pyridine with anti-fibrotic activity) or nintedanib (tyrosine kinase inhibitor), oxygen therapy, pulmonary rehabilitation, or in some instances lung transplant [112]. Recently, prostacyclin analogs [103,113] and phosphoinositide 3-kinase (PI3K) pan inhibitors [114,115] have shown promise in models of PF with examples of both classes of drugs being evaluated via the inhaled route of administration.…”
Section: Nebulized Cl27c For the Treatment Of Pulmonary Fibrosismentioning
confidence: 99%